IMPLEMENTATION OF THE CODE OF CONDUCT OF RADAR BONE JOURNALISTS IN ISLAMIC COMMUNICATION ETHICS PERSPECTIVE - Qudratullah Qudratullah; Syam Syukur (International Conference on Social and Islamic Studies, 2021)
This study aims to analyze the application of the journalistic code of ethics on Radar Bone media from the perspective of Islamic communication ethics. something interesting because it provides another perspective in the field of journalism. More than that when viewed from the point of view of the professionalism of journalists themselves. This research is field research with the method used is descriptive qualitative. The approach used is a communication approach through the study of Islamic communication ethics. Primary data sources were obtained from interviews with the editor-in-chief and journalists of Radar Bone, while secondary data sources were taken from documentationand references relevant to this research. Data were collected by observation, interviews, and documentation. The results of the study indicate that journalists who work at Radar Bone media are fully aware of the level of editorial policy to continue to be applied in the work they are engaged in. Presenting news that is by editorial policies and based on a journalistic code of ethics and Islamic communication ethics, namely Qaulan Sadida (true words), Qaulan Baliga (effective, right on target), Qaulan Karima (noble words), Qaulan Ma'rufa (good words). good, proper), Qaulan Layyina (gentle), Qaulan Maysura (easy to accept). The behavior of a journalist in doing work is a responsibility that shows the professionalism of a journalist in pursuing his profession.